Poor Relief and Charity 1869-1945 - Humphreys, R. author. aut Link
XIII, 228 p.
Keywords: This volume challenges many widely held beliefs about the efficacy of the London Charity Organization Society. Politicians, social administrators, sociologists, economists, biographers and historians have been swayed by the strength of their propaganda. The Charity Organization Society continues to be used as an institutional model to illustrate the alleged advantages of voluntarism over state benefits. Poor Relief and Charity 1869-1945 exposes the misleading nature of many of its claims. It explains why they were shunned by other charities, treated with suspicion by parish clergy, disregarded by poor law guardians and seen as little different from the stigmatized poor law by those in need.